2013
DOI: 10.1021/jp405067y
|View full text |Cite
|
Sign up to set email alerts
|

Sink or Surf: Atmospheric Implications for Succinic Acid at Aqueous Surfaces

Abstract: Small organic compounds are increasingly being invoked as important players in atmospheric processes that occur on aerosol surfaces. The diacid succinic acid is one such constituent that is prevalent in the troposphere, surface active, and also water-soluble. This article presents a thorough examination of the surface characteristics of succinic acid at the vapor/water interface using a combination of theoretical simulation and experiments using vibrational sum frequency spectroscopy and surface tension. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 102 publications
2
53
0
Order By: Relevance
“…However, considering the constant ratio, no significant changes in orientation over the studied concentration range are anticipated. In recent publications by Blower et al 34 and Ruehl et al, 35 where the orientation of succinic acid at the aqueous interface was investigated, supplemental evidence can be found. Their final analysis led to the conclusion that succinic acid in aqueous solution mainly orients with the carboxylic acid groups on the same side of the molecule when looking along its CH 2 -CH 2 -axis, which was also found by Roberts et al.…”
Section: Probing the Surface With Xps: Succinic Acid At Different Promentioning
confidence: 99%
“…However, considering the constant ratio, no significant changes in orientation over the studied concentration range are anticipated. In recent publications by Blower et al 34 and Ruehl et al, 35 where the orientation of succinic acid at the aqueous interface was investigated, supplemental evidence can be found. Their final analysis led to the conclusion that succinic acid in aqueous solution mainly orients with the carboxylic acid groups on the same side of the molecule when looking along its CH 2 -CH 2 -axis, which was also found by Roberts et al.…”
Section: Probing the Surface With Xps: Succinic Acid At Different Promentioning
confidence: 99%
“…NPF involves two distinct steps, i.e., nucleation to form a critical nucleus and subsequent growth of newly formed nanoparticles to a larger size (> 3 nm). Currently, the identities and the roles of chemical species involved in NPF are not fully understood at the molecular level, hindering the development of physically based parameterization to include NPF in atmospheric models (Zhang, 2010;Cai and Jiang, 2017). Sulfuric acid (SA) is believed to be the most common atmospheric nu-8004 Y.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the kinetics and energetics of acid dissociation at the air-water interface are expected to be significantly different than those in bulk water since the intermolecular forces experienced are fundamentally different in interfacial environments than in bulk environments. [5][6][7] For example, both experimental and computational studies have shown that the dissociation energetics and kinetics of HNO 3 change significantly at the water surface. 5,8,9 More specifically, X-ray photoelectron spectroscopy has shown that the degree of dissociation of HNO 3 decreases by B20% at the water surface relative to in bulk water.…”
Section: Introductionmentioning
confidence: 99%